Local Estimates of Singular Solution to Gaussian Curvature Equation (Journal of Partial Differential Equations, 2003)
" In this paper, we derive the local estimates of a singular solution near its singular set Z of the Gaussian curvature equation \u0394u(x) + K(x)e^{u(x)} = 0 in \u03a9 \\ Z, in the case that K(x) may be zero on Z, where \u03a9 \u2282 R\u00b2 is a bounded open domain, and Z is a set of finite points."
Keywords: Singular solution; semi-linear elliptic equation; moving planes